High MYC mRNA Expression Is More Clinically Relevant than MYC DNA Amplification in Triple-Negative Breast Cancer - Eriko Katsuta; Li Yan; Takashi Takeshita; Kerry-Ann McDonald; Subhamoy Dasgupta; Mateusz Opyrchal; Kazuaki Takabe (2019)
DNA abnormalities are used in inclusion criteria of clinical trials for treatments with specific targeted molecules. MYC is one of the most powerful oncogenes and is known to be associated with triple-negative breast cancer (TNBC). Its DNA amplification is often part of the targeted DNA-sequencing panels under the assumption of reflecting upregulated signaling. However, it remains unclear if MYC DNA amplification is a surrogate of its upregulated signaling. Thus, we investigated the difference between MYC DNA amplification and mRNA high expression in TNBCs utilizing publicly available cohorts. MYC DNA amplified tumors were found to have various mRNA expression levels, suggesting that MYC DNA amplification does not always result in elevated MYC mRNA expression. Compared to other subtypes, both MYC DNA amplification and mRNA high expression were more frequent in the TNBCs. MYC mRNA high expression, but not DNA amplification, was significantly associated with worse overall survival in the TNBCs. The TNBCs with MYC mRNA high expression enriched MYC target genes, cell cycle related genes, and WNT/β-catenin gene sets, whereas none of them were enriched in MYC DNA amplified TNBCs. In conclusion, MYC mRNA high expression, but not DNA amplification, reflects not only its upregulated signaling pathway, but also clinical significance in TNBCs.